Pengaruh ibu bapa dan rakan sebaya terhadap kecerdasan dan tingkah laku kanak-kanak prasekolah di Daerah Kluang, Johor - Loh, Sau Yue (2021)
This study aims to determine the influence of parents and peers on the intelligence and behavior of preschool children in the district of Kluang, Johor. In detail this study looked at the influence of parents and peers on the intelligence and behavior of preschool children. Family or parents and peers as socializations influencing the early years of childhood should be models of emotional expression to children and give them opportunities to remember and understand it (Casiddy, ParkeButkovsky & Braungart, 19992; Cummings and Davies, 1994 ; Denham et.al, 1990; Dunn, 1995 and Dunn & Munn, 1987). This study was conducted in quantitative form and aims to study in the district of Kluang, Johor. A total of 130 kindergarten children were randomly selected through the parents of Preschool students in Kluang district, Johor as respondents. Questionnaires were distributed to collect data and analyzed using mean score, correlation, t test, and One-Way ANOVA via SPPS version 26. Part A findings of the peer dimension study (mean = 2.814) and this was followed by Part B supervisory dimension (mean = 2,725). Section C summarizes the level of tendency to quit work among primary teachers (mean = 1.356). While Section D there was no significant difference between male and female teachers with a value of p = 0.232; p> 0.05. For part E there was no significant difference between the level of job satisfaction with a value of p = 0.243; p> 0.05. Finally, Part F of the supervision dimension between Cluster Secondary School and Day Secondary School teachers with a value of p = 0.55; p> 0.05. Some implications and recommendations regarding this study are also discussed.